Alzoubi Distribution: Properties and Applications - Mohammed Benrabia; Loai M. A. Alzoubi (My University, 2022)
In this article, a new two parameters distribution named Alzoubi distribution (AzD) is suggested. Its moments have been obtained. Reliability analysis including hazard rate, cumulative hazard rate and reversed hazard rate functions and the entropy have been discussed, the deviation about mean and median is derived, and the distribution of order statistics is obtained. A simulation study is performed to estimate the model parameters using the maximum likelihood and the ordinary and weighted least squares methods. The goodness of fit to real data set shows the superiority of the new distribution. Keywords: Mixing distribution, Alzoubi distribution, moments, reliability analysis, R´ enyi entropy, maximum likelihood estimation, moment generating function.